Healthy Lifestyle is the Key to A Prosperous Society (International Journal of Scientific Trends, 2024)
The article outlines the ideas that the mental, spiritual perfection of students-youth depends on their physical health, that with the help of physical health, energy, intelligent youth can build and promising Future of our country. Moreover, it analyses extracorporeal spiritual training and new methods of forming a healthy lifestyle among youth